Hagyomány vagy alkalmazkodás, avagy Gilvánfa kívül-belül (Szociológiai Szemle, 2024)
The paper tries to present the alternating periods of integration and segregation, the problems of adjustment of the Gypsies of the settlement and its economic and political context by the historical and contemporary analysis of an ethnically homogenous Gypsy village.In the village of Gilvánfa there are the descendants of two ethnically identical groups. The difference between them is only that much that they have arrived in the village and its vicinity at different times. According to our experience that initial difference has had long-term consequences upon the changes of careers. One of the groups began to approach the society of the village exclusively inhabited by Gypsies in an economically open situation. It offered an opportunity for the development of a symbiotic relationship. Whereas those arriving later got closer to the village already at a period when a large part of the rural families were moving to bigger settlements as a result of rapid economic shrinking so typical of small villages. Differences in the way and style of life could be identified between the two groups up to the most recent times. Today its best indicator is the simultaneous migration of Gypsies from Gilvánfa with the peasants. Today only a few families of them remain in the village.The economic processes of the past decades have again made the inhabitants of this small village homogenous. Today Gilvánfa can be considered as an extremely segregated settlement developing phenomena of a ghetto where in the lack of other possibilities of income the population tries to survive on odd jobs, gathering, family allowance and other social allocations. In an economic situation which has become totally impossible, new modes of differentiation can be observed. The families, called strategy changers by us, break up their family and community relations that have become inconvenient by now (as on those relations community ownership prevails in the face of private one. and the survival of the community dominates over individual progress) as they make economic promotion absolutely impossible. This strategy is followed even at the cost of losing their close relationship to their own parents, sisters and brothers. Instead they build intimate, friendly relations with those pursuing similar strategies. However, in that community, totally blocked, even that way of life does not lead too far. Today an individual economic upliftment has no chance just as much as that of the upliftment of the entire community.We wish to highlight - without entering into a totally ahistorical exposition of ‘if - then’ that an economically open situation has made upliftment and adjustment possible jointly, as a community of Gypsies. Whereas emergence from an economically closed, spatially and socially totally isolated situation cannot be realised even at the cost of total assimilation.